Taxonomic assessment of Australian Eocyzicus species (Crustacea: Branchiopoda: Spinicaudata) - Tippelt, Lisa; Schwentner, Martin (Zootaxa, 2018)
Herein we describe nine species of Eocyzicus from Australia and re-describe the morphological variability of Eocyzicus parooensis Richter & Timms, 2005 and Eocyzicus argillaquus Timms & Richter, 2009. All species were previously delimited by molecular phylogenetic analyses and the species descriptions are based on the same individuals. Characters were scored with the aid of the taxonomic software DELTA. The morphological analyses largely corroborated the previously delimited species despite high levels of intraspecific variability that overlapped with interspecific variation in many instances. Morphological species delimitation was generally supported by principal component and canonical variate analyses. Characters best suited for morphological species identification were the numbers of growth lines on the carapace, the number of telsonic spines and the number of setae on the furca.